Pengaruh Harga, Kualitas Layanan, dan Kepercayaan Terhadap Loyalitas Pelanggan Jasa Angkutan Umum (Studi Pelanggan Bus Batik Solo Trans) - Kuncoro, Haryoseno; , Dra. Chuzaimah,MM (2016)
The purpose of this study is to find the influence of prices, service quality, trust towards customer loyalty in public transport services a study of customers Batik Solo Trans bus. Methods used in this research is descriptive analysis, validity test, reliability test, the classics assumption test (normality test, multicollinearity test, heteroskedasticity test, and autocorrelation test), multiple linear regression analysis, and hypothesis test (t test, F test and coefficients determination). In this research is based on t test obtained price variable partially have an significantly to customer loyalty, service quality variable partially have an significantly to customer loyalty,trust variable partially have an significantly to customer loyalty. The F-test based on the influence of price, quality of service and trust on customer loyalty, there are significant influence jointly between the price, service quality, and trust in customer loyalty. Based on test results obtained R2 value of Adjusted R Square of 0.634 or 63.4%, so it can be concluded the price, quality of service and the trust is able to explain the variations of customer loyalty by 63.4%, while the remaining 36.6% is explained by other variables outside the model researched. Keywords : Consumer Loyalty, Price, Service Quality, Trust